PERAN KOMITMEN ORGANISASIONAL MEMEDIASI PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP OCB - Santi, Ketut Savira Purnama; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen; Vol 8 No 7 (2019)DO - 10.24843/EJMUNUD.2019.v08.i07.p09, 2019)
The purpose of this study was to determine the effect of transformational leadership on organizational commitment, to determine the effect of transformational leadership on Organizational Citizenship Behavior (OCB), to determine the effect of organizational commitment on Organizational Citizenship Behavior (OCB), and to determine the role of organizational commitment in mediating the effect of transformational leadership towards Organizational Citizenship Behavior (OCB). This research was conducted at PT. Nadia Kencana. The number of samples used in this study is 78 people using the saturated sample method (census), which uses the entire population as a sample. Data analyzed using path analysis techniques The results showed that transformational leadership has a positive and significant effect on organizational commitment at PT. Nadia Kencana, transformational leadership has a positive and significant effect on Organizational Citizenship Behavior (OCB), organizational commitment has a positive and significant effect on Organizational Citizenship Behavior (OCB), and organizational commitment positively and significantly mediates transformational leadership on Organizational Citizenship Behavior (OCB) at PT. Nadia Kencana. Keywords: transformational leadership, organizational commitment, OCB